Fundamental applications of Internet of Things - Chowdhury, Md. Monwar Jahan; Jesan, Md. Fazlul Haque; Milon, Md. Saiful Islam (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.